Potential screening strategies for early prediction of pre-eclampsia - K., Hymavathi; Davuluru, Sandhya Rani; Shaik, Sameera; Kaviti, Sahithi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: This study was conducted to evaluate the efficacy of different biochemical and biophysical markers in the early weeks of gestation as screening tools for early prediction of preeclampsia. Methods: This hospital-based prospective observational study conducted on 52 pregnant women, at less than 13 weeks of gestation were recruited. Maternal serum inhibin A and USG uterine artery PI levels were analyzed among the pregnant women who subsequently developed PE and compare with those who did not develop PE. Methods used for the detection of markers were: chemiluminescence immunoassay (CLIA) for serum inhibin A levels, and uterine artery Doppler velocimetry was done by PHILIPS HD11XE transabdominal ultrasound machine using a 4-6 MHz probe with the same sonographer. Results: The present study revealed a significant rise of inhibin A in preeclamptic women when compared to normotensive women (p<0.0001). The mean levels of 1st and 2nd trimester uterine artery PI significantly high in women who subsequently developed PE when compared to those who did not develop preeclampsia (p<0.0001). Study results showed a strong association between gestational age at delivery and neonatal outcome (neonatal birth weight and APGAR) with preeclampsia. The maternal serum inhibin A, and uterine artery PI found to have good sensitivity and specificity for early prediction of PE. Conclusions: Study concluded that the women who are prone to develop PE subsequently, had high levels of MAP, UAPI, inhibin A. In our setting, MAP, UAPI, inhibin A, appeared to be better screening modalities. Combination of the biochemical markers with the biophysical markers, demographic characteristics, and other novel markers will establish the effective screening models for early prediction of PE. Early identification of high-risk cases will offer an opportunity for prophylactic therapy, such as Low- dose Aspirin in selected groups of high-risk women screened in the first trimester, thus improving the maternal and perinatal outcome.